Knyga ir bibliografinė informacija - Bespalova, Emilija (Knygotyra, 1986)
The problem "the bibliography and the book work" is not elucidated to the end.This article deals with the analysis of different kinds of activity (primary and secondary) formed historically during the process of creation of the modern book. Due to the secondary kind of work a secondary information about the book itself is found in the book. The secondary (bibliographical) information ensures the circulation of books in the society. The bibliographical information in a book (the so called affined information) is the base of the bibliographical activity which produces an independent (diagenetical) document called a bibliographic book.Bibliological view on the bibliographical system permits to study the history of its evolution in close connection with the history of the book printing and the book trade. The bibliographical craft and the bibliographical documents became the part of the social structures confined by the time and the territory. The general differentiation of the world bibliographical process started. The differentiation of the bibliographical systems into subsystems confined by the time and the territory is the starting point of the general differentiation. After that a more versatile differentiation of the bibliographical craft followed.